Comparison of Different Quantitative Methods and Visual Evaluation on the Tc-99m-HMPAO Brain Perfusion SPET - Kekilli, Ersoy; Yağmur, Cengiz; Ertem, Kadir; Turgut, Songül; Aydın, Ömer Murat (Fırat University, 2006)
Objectives: Brain perfusion SPECT has been widely used for evaluation of brain perfusion and metabolic status. We aimed to compare different quantitative methods on Tc-99m-HMPAO SPET based on visual evaluation. Materials and Methods: Forty-seven patients were enrolled in this comparative study. Tc-99m-HMPAO brain SPET was performed. For semiquantitative analysis, two orbitomeatal (OM) composite slices were obtained. Regional cerebral perfusion data were semi-quantitatively computed by the ratio between each cerebral ROI mean-counts and the reference region mean-counts. Mean counts of the cerebellum, mean-counts of lower OM slice and contralateral ROI mean-counts were used as reference regions. Two different nuclear physicians evaluated all images. It was considered 0 (=hypoperfusion area); 1 (=normal perfusion area) and 2 (=hyperperfusion area) by visual evaluation. SPET slice's region of interest (ROI) data were analyzed by receiver operator characteristics (ROC) method to establish the optimal decision threshold for different quantitative methods. Results: Our results observed that usage of small ROIs were better than larger ones. The mean-counts of lower OM slice had a positive correlation with the cerebellum mean-count. Additionally, as reference regions, mean-counts of lower OM slice was slightly better than cerebellum and evidently better than symmetric region of the contralateral hemisphere. Conclusion: We did not found the expected high correlation among visual analysis and these quantitative methods. We believe that new quantitative methods on the Tc-99m-HMPAO brain perfusion SPET are required. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Beyin perfüzyon sintigrafisi beyin perfüzyonu ve metabolik durumunu değerlendirmek için yaygın olarak kullanılmaktadır. Biz görsel değerlendirmeye dayanarak Tc-99m-HMPAO SPET'deki farklı ölçüm metodlarını karşılaştırmayı amaçladık. Gereç ve Yöntem: Kıyaslamalı çalışmamıza 47 hasta dahil edildi. Tc-99m-HMPAO beyin perfüzyon SPET uygulandı. Yarı-kantitatif analiz için iki orbitomeatal (OM) compozit kesit oluşturuldu. Bölgesel serebral perfüzyon bilgileri semi-kantitatif olarak her bir serebral ROI ortalama sayımı ve referans bölge ortalama sayımı arası oran olarak hesaplandı. Serebellum sayım ortalaması, alt OM kesit sayım ortalaması ve karşı hemisfer ilgi alanı sayım ortalaması referans bölgeler olarak kullanıldı. İki nükleer tıp uzmanı bütün görüntüleri değerlendirdi. Görsel değerlendirmede ilgi alanlarını 0 (=hipoperfüze alan); 1 (=normal alan) ve 2 (=hiperperfüze alan) olarak tanımladı. SPET kesiti ilgi alanları bilgileri farklı ölçüm metotlarının ideal karar eşiğini temin metodu olan ROC analizle değerlendirildi. Bulgular: Bizim bulgularımız küçük ilgi alanları almanın büyük ilgi alanlarından daha iyi olduğunu gösterdi. Alt OM kesit sayım ortalaması serebellum sayım ortalaması ile pozitif korelasyona sahipti. Ek olarak, referans alan olarak, alt OM kesit sayım ortalaması kullanımı serebellumunkinden hafif; karşı hemisfer simetrik alanınınkinden ise belirgin daha iyiydi. Sonuç: Biz görsel değerlendirme ile bu ölçüm metotları arasında beklediğimiz yüksek uyumluluğu bulamadık. Beyin perfüzyon Tc-99m-HMPAO SPET te yeni ölçüm metotlarına ihtiyaç olduğunu düşünmekteyiz. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Tc-99m-HMPAO beyin perfüzyon SPET'inde farklı ölçüm metodları ve görsel değerlendirmenin karşılaştırılması